Fight Narcotics with Community Strengthening: Crime Control Management by Community Policing - Pasaribu, Restiana (Universitas Negeri Semarang, 2018)
Drugs are the main enemy of nations in the world. Indonesia, it seems also has become a paradise for the generation of drugs. Various problems that occur in the community that can be resolved kinship will be resolved in RT Polmas assisted by community figures in the surrounding community. Thus, the empowerment of Polmas by Polrestabes Semarang city in the prevention of drug crime is crucial to be the main program Polrestabes Semarang city. The research location is in Polrestabes Semarang. This research emphasized that Policing Empowerment in Criminal Drugs Control is expected to provide active support to the Polmas to report it if there is any indication that the drug is involved in its territory and dare to disclose its circulation, arrest the dealer, the perpetrator and the producer. Cooperation and coordination and involvement of the above mentioned community participation must be optimally empowered, in order to support the success of the prevention of criminal acts of narcotics.